THE DETERMINATION OF THE DEPTH OF TPI PALANG’S HARBOUR BASIN TUBAN THROUGH CALCULATION OF TIDE COMPONENT - Joesidawati, Marita Ika (Jurnal Segara, 2024)
Determination of the datum chart using the tide component can be used to determine the depth of the harbour basin. TPI Palang's harbour basin is often used as a place for mooring fishing boats, but it often happens that the ships get stuck before entering the haarbour basin. The type of fishing ship at the TPI Palang harbour basin is a payang boat with a draft depth of 2 m. The depth of the harbour basin measurement results in July 2017 was 8 m, while based on the bathymetric map is 12 m. Palang waters, in Tuban Regency is located in the North Sea of East Java, which is open water type, therefore the determination of the depth of the harbour basin is based on the state of the water, is 1.2 x ship draft, which is 2.4 m. The least square and the admiralty method were used to compare the best method in calculating the tidal component. Researchers used tidal data for August 2016- July 2017 obtained from BIG. The tidal type of the Palang waters is diurnal, with an F value for admiralty treatment of 5,160 with least square processing of 5,167. The correlation coefficient of the tidal component with admiralty processing occurs in K1-MS4 of 0.792, while the least square occurs in K1-M4 of 1.6. The result of the calculation of the tidal component of the least square is used to determine the value of the datum chart. The IHO (International Hydrographic Organization) datum chart is used as a basic reference for calculating the depth of the TPI Palang harbour basin. The results show that the required depth of Palang waters in the existing condition (8 m) still requires dredging between 0.033 - 1.071 m. However, to meet the standard of the harbour basin, the required depth is 13,071 m (from LWS) to 13,557 m (from LLWS) which means that the dredging of the harbour basin is about ± 4 m.